MOVING OUT OF POVERTY MODEL THROUGH COMMUNITY EMPOWERMENT (Study of littoral communities in Makassar) - Dahliah Dahliah; Serlin Serang; Ajmal As’ad (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2020)
The aims of this study; 1) to analyze the poverty levels of littoral communities in Makassar. 2) To reinforce the economic sector based on littoral potency by Moving Out of Poverty (MOP) model along with government programs. 3) To utilize the potential and empowerment of littoral communities. Seemingly, poverty as deficient conditions by individuals or communities. Conceptually, this study was conducted by a quantitative paradigm with a case study approach. The data obtained from observations, depth interviews, and questionnaires. The studies showed that: there was a significant effect in strengthening the quality of the human resources to empowerment. Subsequently, no significant effect between economic institutions to empowerment, There was a significant effect between fishing gear or production equipment to empowerment, There was not a significant effect in improving the quality of the human resources to Moving Out of Poverty (MOP) by empowerment, There was no effect between economic institutions and Moving Out of Poverty (MOP) by empowerment, There was no effect of fishing gear to Moving Out of Poverty (MOP) significantly, There was no significant effect between education to Moving Out of Poverty (MOP).